RANCANG BANGUN MEDIA BERBASIS KARTU PERMAINAN KOLEKSI BERTEMA FLORA DAN FAUNA DI INDONESIA - Alatas, Muara; Prihantini, Prihantini (Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The background of this research focuses on the use of the lecture method which is often used by class teachers in teaching and is too dependent on the availability of students' books. The aim of this research is to produce a collection of game card-based media with the theme of flora and fauna in Indonesia as an alternative media for social studies learning in elementary schools. The research method used is Design and Development (D&D) using procedures from N.J. Manson. The participants involved are validators consisting of material experts, media quality experts, and design experts; The respondents involved were class teachers at SDN 227 Margahayu Utara and SD Laboratory UPI Cibiru Campus. The results of this research are products in the form of printed collectible game cards with the theme of flora and fauna in Indonesia which have gone through a validation and assessment process from respondents. The validation results show that the collection game cards are in the